2014
DOI: 10.3892/mmr.2014.1974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin I-converting enzyme and α-actinin-3 gene polymorphisms on sport performance

Abstract: Genetic polymorphism is considered to be associated with human physical performance. The angiotensin I-converting enzyme insertion/deletion (ACE I/D) and the α-actinin-3 gene (ACTN3) R577X polymorphisms have been widely investigated for such associations, and functional ACE I/D and ACTN3 R577X polymorphisms have been associated with sprinter performance. The aim of this study was to determine the effect of these polymorphisms on sport performance among 37 elite athletes and 37 healthy controls. The ACE II geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
0
13
0
6
Order By: Relevance
“…Increased ACE level/activity, observed in persons with the DD genotype, is associated with increased blood pressure, and also with a higher risk for many other cardiovascular disorders (Wang and Staessen 2000). Additionally, a number of studies have suggested that ACE insertion is associated with better endurance performance in elite athletes (Ma et al 2013;Gunel et al 2014;Saber-Ayad et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Increased ACE level/activity, observed in persons with the DD genotype, is associated with increased blood pressure, and also with a higher risk for many other cardiovascular disorders (Wang and Staessen 2000). Additionally, a number of studies have suggested that ACE insertion is associated with better endurance performance in elite athletes (Ma et al 2013;Gunel et al 2014;Saber-Ayad et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(20) benzer bir şekilde farklı disiplinlerden oluşan 37 elit atlet ve aynı sayıdaki kontrol grubu üzerinde yaptıkları çalışma-da ACTN3 XX ve RX genotipini sporcu grubunda sırasıyla %35,14 ve %54,05 olarak bulmuşlardır. Çalışmalarında RX genotipini, hem sporcu grubu, hem de sedanter kontrollerde yüzde olarak en yüksek genotip değeri olarak bulmuşlardır.…”
Section: Introductionunclassified
“…Other studies have suggested that allele I can influence the performance of athletes of aerobic sports predominantly, whereas allele D would be related to events which strength-power is the most demanded physical capacity. 1,[12][13][14][15] However, results involving athletes, both of endurance and strength-power, and control groups from different continents have presented different frequencies of ACE genotypes, 12,16,17 which generates controversy in literature.…”
Section: Introductionmentioning
confidence: 99%